(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2016)
In today’s digital era mobile commerce is growing at a very fast pace. It is contributing to the growth of e-commerce sales in India. Mobile commerce is driving the revenue of retailers. The way customers’ shop is changing due to the way technology isused in the shopping process. The purpose of this paper is to investigate the factors that influence customers’ to adopt mobile shopping.Data is collected from West Delhi. Factor analysis is used to extract factors that influence customers’ to adopt mobile shopping. The results demonstrate that the most important factors are Perceived Usefulness, Trust, Incentives, Convenience, Consumption experience, Self -efficacys and Subjective norms. The findings of the study helps to understand what encourages the customers’ for mobile shopping .The result also helps retailers in developing their strategies to encourage mobile shopping in India.